INTERNALISASI PENDIDIKAN IMAN KEPADA ANAK DALAM PERSPEKTIF ISLAM - Silahuddin Silahuddin (Jurnal Ilmiah Didaktika, 2016)
Children are human beings who are in need to be nurtured, guided and developed. All of their potency should be developed positively in education. Educating childrenâ€™s faith by using LuqmÄn al-á¸¤akÄ«m ways will lead them to be the most precious blessing creatures in this world and the hereafter. Keywords: